Strategi Optimalisasi Penagihan Tunggakan Pajak Daerah melalui Pendekatan SWOT dan TPB: Studi di Bapenda Kota Dumai - Hua, Me; Ratnawati , Vince; Azlina, Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study aims to analyze the obstacles, optimal strategies, and success factors for collecting local tax arrears in Dumai City Government. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation at Bapenda Dumai. The main obstacles include the lack of human resources, low taxpayer awareness, and minimal socialization. The strategies implemented include the TANJAK (Direct Tax Collection) program, socialization through the media, persuasive collection, validation of arrears with third parties, cooperation with the Prosecutor's Office, and tax relaxation programs. The SWOT analysis shows strengths such as regulatory support and infrastructure, but weaknesses in limited human resources and socialization. Opportunities in the form of technological advances and cross-agency cooperation can be utilized, while threats in the form of negative perceptions and high arrears must be overcome.